Summary of Baseline Household Survey Results: Ek Phnum district Battambang province Cambodia - Eam, Dyna; Vuthy, Chin; Ferrer, Alice J.; Tan Yen, Bui; Yumiko, Kura; Sebastian, Leocadio S. (2015)
The household baseline survey conducted from December 2014 to January 2015 collected data from 140 households in seven villages, including Rohal Suong village, in the Ek Phnum district, Battambang province, Cambodia. This is part of the baseline data collection activities in Rohal Suong Climate Smart Village of CGIAR Research Program on Climate Change, Agriculture and Food Security. The objective is to collect household baseline data where the data to be collected five and 10 years after on the same households will be compared to capture changes that may occur over time. Results showed that the households were highly dependent on farming and small livestock raising for food and income and had access to small landholdings. Households also diversified income sources by engaging in off-farm work, and experienced hunger, especially in the months of October to December. Farming was characterized by low crop and commercialization index. Climate change-related factors, particularly drought and flooding, were the main factors identified to influence farming decisions. Adaptation and mitigation measures need to be enhanced. Information on extreme weather events were commonly available, but not weather forecasts. Providing the farmers with correct information can help them make good farming decisions.